Regulation of carbon and phosphorus content in manganese alloys when processed in an oxidizing gas environment or oxide system - Velychko , K.O.; Mianovska , Ya.V.; Kamkina , L.V. (Theory and Practice of Metallurgy, 2024)
Purpose: Determination of rational methods for reducing the carbon and phosphorus content in manganese alloys. Research methodology: Thermodynamic calculations and experimental studies of decarbonization and dephosphorization of a high-phosphorus manganese alloy. Research materials: As a high-carbon ferromanganese with a high phosphorus content, a related metal (manganese alloy) obtained during the production of low-phosphorus slag at the Nikopol Ferroalloy Plant was used. Rolling scale was used as an oxidant, with a composition of FeO - 59.5 wt. %; Fe3O4 - 38.9 wt. %. Research results: The features of dephosphorization of manganese alloys are considered. According to the adopted "classical" technology, a useful product of dephosphorization of manganese concentrates is manganese slag with a low phosphorus content. Oxidation of phosphorus dissolved in the metal can occur as a result of its interaction with oxygen in the gas phase. The higher the basicity of the manganese slag, the greater the probability of phosphorus oxidation. Given the basicity of the slag, the higher the FeO content in it, the better the conditions for removing phosphorus from the metal. The process of dephosphorization of the associated metal includes the oxidation of phosphorus, the binding of phosphorus oxide into strong compounds (phosphates) and their transition to the slag phase. Scientific novelty: The associated metal includes silicon, which has a much higher affinity for oxygen than phosphorus; then, naturally, it will first be oxidized with the formation of silicon oxide with a melting point much higher than the temperature of experimental studies. Practical significance: The results obtained show that when oxidizing the associated metal with iron scale at a specific consumption of 114 kg/t of metal, the total degree of silicon extraction was 88.16%, phosphorus - 71.03%. At the same time, the manganese content in the metal decreased by 6.48% due to the recovery of rolling scale.